Lateralization of cerebral blood flow in the auditory cortex of patients with idiopathic tinnitus and healthy controls: An arterial spin labeling study - Li, Xiaoshuai; Zhao, Yansheng; Hui, Ying; Wu, Yuntao; Chen, Qian; Shi, Huijing; Lv, Han; Li, Mengning; Zhao, Pengfei; Zhang, Wenfei; Zhao, Xinyu; Li, Jing; et al. (Frontiers in Neuroscience, 2022)
Objectives To assess the lateralization of cerebral blood flow (CBF) in the auditory cortex of idiopathic tinnitus patients and healthy controls (HCs) using 3D pseudocontinuous arterial spin labeling (pcASL). Methods Thirty-six patients with idiopathic tinnitus and 43 sex- and age-matched HCs underwent 3D-pcASL scanning using a 3.0 T MRI system. For both groups, region of interest analysis was performed on the primary auditory cortex (PAC), auditory associative cortex (AAC), and secondary auditory cortex (SAC). The clinical data of all subjects were analyzed. Results In both tinnitus patients and HCs, CBF of the left PAC was significantly higher than that of the right (HCs: P = 0.02; patients: P = 0.043), but CBF of the right AAC and SAC was significantly higher than that of the left (AAC: HCs, P < 0.001; patients: P < 0.001. SAC: HCs, P < 0.001; patients: P = 0.001). Compared with HCs, tinnitus patients exhibited significantly higher CBF in the bilateral PAC (right: P = 0.008; left: P = 0.022). CBF in the left PAC was positively correlated with tinnitus severity (r = 0.399, P = 0.016). Conclusion This study confirms the asymmetry of the auditory cortex and investigates the underlying neuropathology of idiopathic tinnitus in terms of CBF.